Antenatal scoring system in predicting the success of planned vaginal birth following one previous caesarean section. (3rd April 2018) - Kalok, Aida; Zabil, Shahril A.; Jamil, Muhammad Abdul; Lim, Pei Shan; Shafiee, Mohamad Nasir; Kampan, Nirmala; Shah, Shamsul Azhar; Mohamed Ismail, Nor Azlin
Abstract: This was a prospective observational study to determine the predictive factors for a successful vaginal birth after caesarean section (VBAC) and to develop a relevant antenatal scoring system. Patients with one previous caesarean section were included in this study. All data including maternal demographics, obstetric history, pregnancy progress and outcomes were collected and analysed. A total of 142 out of the 186 women (76.3%) had successful VBAC. History of previous vaginal delivery and non-recurrent indications for previous caesarean section were the significant predictive factors for a successful VBAC. Five variables for our scoring tool were selected. By using a proposed mean score of 4 out of 7, the scoring system had a sensitivity of 81.0%, specificity of 52.3% and a positive predictive value of 84.6%. VBAC antenatal scoring system was potentially a useful predictive tool in antenatal counselling. Impact statement: What is already known on this subject: Planned vaginal birth after caesarean section (VBAC) is an important strategy to limit the overall caesarean section rate, which is related to maternal morbidities. However, trial of vaginal delivery does involve potential complications including scar dehiscence, postpartum haemorrhage and emergency hysterectomy. What the results of this study add: Clinical predictors of a successful VBAC include non-recurrent indications for the previous caesarean section, previous vaginal delivery, spontaneous onset of labour and birthweight less than 4kg. There were multiple screening tools developed to predict the likelihood of successful VBAC. These scoring systems involved various variables such as age, ethnicity, Bishop's score and previous caesarean indication. We had prospectively developed an antenatal scoring system based on five variables. Our result showed that patient with a score of four and above will have around 85% chance of successful VBAC. What the implications are of these findings for clinical practice and/or further research: We have also found that, estimated foetal weight based on ultrasound scan is a potential predictor for successful VBAC. This simple scoring method will be useful in-patient counselling regarding mode of delivery after one previous caesarean section. A multicentre study involving large cohort of patients is ideal to validate our scoring system.